Design and Performance Analysis of B-Series Propeller for Traditional Purse Seine Boat in the North Coastal Region of Central Java Indonesia - Windyandari, Aulia; Haryadi, Gunawan Dwi; Suharto, Suharto; Abar, Insanu Abdilla Cendikia (Journal of Applied Engineering Science, 2018)
In the North Coastal Region of Central Java, the traditional fishing boat is a primary object that generates the economics activities of the social community. As an artisanal fishery, the boats generally adopt the tradition to build technique from their predecessor. Therefore the lack of practice to determine the propeller design which considered the hydrodynamic relation within the boat dimension, hull form geometry and propeller is observed. Presently, there is no a standard propeller design that particularly well designed considering the hull shape geometry for the traditional boat. The aim of the research is to develop standard propeller that would be applied to the fishing boats typically found in the North Coastal Region of Central Java using B-Series marine propeller. Computational Fluid Dynamics (CFD) analysis for assessing the performance of thrust and torque of the developed propeller was performed. The results of analysis show that the optimum propeller is achieved by 4-bladed propeller design which is generate the thrust force of 27.42 kN and the torque coefficient of 0.414 which provide torque moment of 4.01 kNm at the 750 RPM condition. It can be concluded that the proposed 4-bladed propeller design have shown a better propulsion efficiency for the traditional purse seine boat.